Care provider perspectives on medical travel: A three-country study of destination hospitals. Issue 1 (2nd January 2016) - Garman, Andrew N.; Johnson, Tricia J.; Lynch, Elizabeth B.; Satjapot, Siriporn
ABSTRACT: Despite growing interest in the current and potential role of medical travel in U.S. patient care, very little research has been conducted on clinician and other provider organizations' perspectives on providing international patient care. The present study sought to gain formative insights about medical travel from the providers' perspectives, by conducting structured interviews and focus groups in six hospitals from three countries catering to patients traveling from the United States. Findings highlighted the surprising role of international events and policies in the evolution of medical travel, as well as both the desire and need for more transparent quality standards.